1993
DOI: 10.1021/jm00054a008
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl-substituted prostaglandins: potent and selective antiglaucoma agents

Abstract: A series of phenyl-substituted analogues of prostaglandin F2 alpha (PGF2 alpha) were prepared and evaluated for ocular hypotensive effect and side effects in different animal models. In addition, the activity of the analogues on FP receptors was studied in vitro. The results were compared with those of PGF2 alpha and its isopropyl ester. The phenyl-substituted PGF2 alpha analogues exhibited good intraocular pressure reducing effect, were more selective, and exhibited a much higher therapeutic index in the eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 9 publications
(16 reference statements)
1
70
0
1
Order By: Relevance
“…Elevated intraocular pressure (IOP) is a primary risk factor for glaucomatous progression, and lowering IOP has been proven effective in modifying the progressive damage [2] . Prostaglandin analogues are the most potent of currently available ocular hypotensive medications [3][4][5][6] . Introduced in 1996, latanoprost was the first prostaglandin F 2 ␣ analogue to become available worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated intraocular pressure (IOP) is a primary risk factor for glaucomatous progression, and lowering IOP has been proven effective in modifying the progressive damage [2] . Prostaglandin analogues are the most potent of currently available ocular hypotensive medications [3][4][5][6] . Introduced in 1996, latanoprost was the first prostaglandin F 2 ␣ analogue to become available worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The PGF 2a prostaglandins, a kind of the most effective antiglaucoma drugs at present, attracted synthetical chemists' and medicinal chemists' research interest [1][2][3][4]. The aim of the present work of our research group was to search for a convenient and cheap strage to synthesize this kind of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…L ong-term treatment with prostaglandins such as PGE 2 , PGF 2a and latanoprost (13,19, -isopropyl ester) a new drug for glaucoma treatment (Stjernschantz & Resul 1992;Resul et al 1993;Stjernschantz & Alm 1996) has been shown to induce increased iridial pigmentation in monkeys (Selén et al 1997). Similar changes have also been seen in patients with heterochromic eye colour during chronic treatment with latanoprost (Wistrand et al 1997), and with isopropyl unoprostone, another PGF 2a analogue (Yamamoto & Kitazawa 1997).…”
mentioning
confidence: 90%